Development and characterisation of a functional beverage from red-fleshed Japanese plums (Prunus salicina L.) - Steyn, Naomi (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc Food Sc)--University of Stellenbosch, 2011.